2016
DOI: 10.1111/ggi.12685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a change in social activity on quality of life among middle‐aged and elderly Koreans: Analysis of the Korean longitudinal study of aging (2006–2012)

Abstract: Consistent participation in religious activities, friendship organizations, leisure/culture clubs, family/school reunion ,and volunteer work improves quality of life among middle aged and older Koreans. Geriatr Gerontol Int 2017; 17: 132-141.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
(82 reference statements)
1
20
1
4
Order By: Relevance
“…The finding that decline in social participation leads to negative mood in both older men and women across different marital groups was consistent with studies that discovered the protective role of social participation in maintaining emotional and mental health, and life quality in older adults . For instance, an 18‐year longitudinal study showed that initiating or continuous participation in social activities significantly reduced depressive symptoms in Taiwanese older adults .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The finding that decline in social participation leads to negative mood in both older men and women across different marital groups was consistent with studies that discovered the protective role of social participation in maintaining emotional and mental health, and life quality in older adults . For instance, an 18‐year longitudinal study showed that initiating or continuous participation in social activities significantly reduced depressive symptoms in Taiwanese older adults .…”
Section: Discussionsupporting
confidence: 85%
“…For instance, an 18‐year longitudinal study showed that initiating or continuous participation in social activities significantly reduced depressive symptoms in Taiwanese older adults . The Korean Longitudinal Study of Aging (2006–2012) further showed that consistent participation in social activities significantly improved the quality of life of older Koreans …”
Section: Discussionmentioning
confidence: 99%
“…In this context, most studies in Korea have examined factors affecting employment or the desire of older adults to return to employment [ 3 , 21 – 23 ], while few studies have explored the effect of elderly employment programs on the QOL of older adults, or the impact of employment on the QOL of older adults [ 9 , 18 ]. However, to improve the lives of the elderly, who comprise an increasing proportion of the population, it is important to identify patterns of change of QOL over time and in relation to employment in Korean society.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that older adults who participate in social groups have significantly higher QoL than non-participants, namely in the physical, environmental and social relations domains of the WHOQoL-Bref and in the past/present/future activities, intimacy and social participation facets of the WHOQoL-OLD 20,21 . Longitudinal studies show that participating in social activities leads to better QoL 22,23 , life satisfaction and self-esteem 24 and reduces depressive symptoms 23,24 in older adults. Moreover, this relationship seems practicing physical activity in the CIP had a significantly higher QoL in the psychological, social relationships and environment domains ( p<0.05).…”
Section: Introductionmentioning
confidence: 99%